SAFEGUARDING THE ENVIRONMENT: INSIGHTS INTO BIOMEDICAL WASTE MANAGEMENT PRACTICES AMONG SAUDI NURSING STUDENTS - Al-Masry , Mahmoud Ali Abdel-Rahman (Research Journal of Health, Medicine and Nursing, 2024)
Biomedical waste (BMW) is any waste generated during the diagnosis, treatment, or immunization of humans or animals. BMW can be classified into general waste, pathological, radioactive, chemical, infectious, sharps, and pharmaceuticals. BMW management is essential to protect human health and the environment. The proper BMW management process includes handling, segregation, mutilation, disinfection, storage, transportation, treatment, and disposal. BMW management is still in its infancy in many parts of the world. This is due to a number of factors, including lack of awareness, lack of resources, and lack of enforcement. The purpose of this review is to provide an overview of BMW management, including its importance, challenges, and best practices.